Posttranslational Modifications of Smurfs: Emerging Regulation in Cancer - Yang, Longtao; Zhou, Wenwen; Lin, Hui (Frontiers in Oncology, 2021)
Smad ubiquitin regulatory factors (Smurfs) belong to the Nedd4 subfamily of HECT-type E3 ubiquitin ligases and strictly control tumor biological processes, including cell growth, differentiation, apoptosis, polarization, epithelial mesenchymal transition (EMT), and invasion. Disruption of Smurf activity has been implicated in cancer progression, and Smurf activity is controlled by a series of posttranslational modifications (PTMs), including phosphorylation,ubiquitination,neddylation, sumoylation, and methylation. These modifications regulate the functional expression of Smurfs by affecting protein degradation and protein interactions. In this review, we summarize the complexity and diversity of Smurf PTMs from biochemical and biological perspectives and highlight the understanding of their roles in cancer.